2023
DOI: 10.1186/s13018-023-03766-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and prediction nomogram model for postoperative hemoglobin < 80 g/L in patients following primary lumbar interbody fusion surgery

Abstract: Objective To analyze the association between different postoperative hemoglobin (Hb) levels and postoperative outcomes in patients who have undergone primary lumbar interbody fusion, and to investigate the risk factors and establish a predictive nomogram mode for postoperative Hb < 80 g/L. Methods We retrospectively analyzed 726 cases who underwent primary lumbar interbody fusion surgery between January 2018 and December 2021in our hospital. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[23][24][25] Recent studies have shown that low Hb is an independent risk factor for prolonged LOS. [26][27][28] However, this finding remains controversial. Some studies have demonstrated a correlation between low Hb levels in hip fracture patients and prolonged LOS, [29,30] while a retrospective study by Song et al with 1112 participants revealed no association between Hb levels before surgery and hospital stays.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…[23][24][25] Recent studies have shown that low Hb is an independent risk factor for prolonged LOS. [26][27][28] However, this finding remains controversial. Some studies have demonstrated a correlation between low Hb levels in hip fracture patients and prolonged LOS, [29,30] while a retrospective study by Song et al with 1112 participants revealed no association between Hb levels before surgery and hospital stays.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…Lumbar interbody fusion is a classic surgical procedure widely utilized both domestically and internationally for the treatment of degenerative lumbar spine disorders such as lumbar disc herniation, lumbar spinal stenosis, and lumbar spondylolisthesis (Ristagno et al, 2018;Tang et al, 2020). This type of surgery provides spinal stability by eliminating nerve compression, which can significantly relieve nerve root symptoms and pain (Guan et al, 2022;Xiong et al, 2023). However, blood transfusions are frequently required during the perioperative period since the surgical procedure is highly intrusive and necessitates complete dissection of the paravertebral soft tissue as well as excision of the lamina and intervertebral disc (Suk et al, 1997;Nuttall et al, 2000;Salehi et al, 2004;Willner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%